O papel dos municipios na gestao florestal: licoes dos estudos de caso - Toni, F.; Kaimowitz, D. (A.S. Editores, 2003)
Since the end of the 1990s, municipal governments are increasingly adopting a pro-environment/pro-forest discourse in Amazonia. In most cases, a strengthening of the local administrative and technical agencies that deal with environment, forest, and land use follows this change in the discourse. In part, this is due to an evolution of the overall political and social context in the country, but also to a few programs and policies that either help or demand changes in local government. For the same reasons, municipal environment and development councils are becoming popular throughout the region. Changes in discourse and administration do not necessarily translate into changes in action. Some municipalities have skilled technical staff, modern equipment and money, but fail to implement sound environmental policies. The mayors have an overwhelming influence over the municipal agenda and are able to prevent popular participation in policy making. This problem is aggravated in municipalities on the agricultural frontier, where land ownership is concentrated, and local elites thrive on the predatory use of natural resources – such as illegal logging and extensive ranching. On the other hand, in municipalities where land use is not experiencing fast change, and where social movements are strong, the local government has a more positive role in forest management. In general, local governments have a very strong indirect influence on land and resource use by means of road building and lobbying for rural credit. Some are engaged in promoting agroforestry, forest certification, and other sustainable practices. Very few local governments show interest in using their prerogatives to establish and manage protected areas, which are considered a barrier to development.